Patterns of care and survival for lung cancer: Results of the European population-based high-resolution study - Sant, Milena; Daidone, Caterina; Innos, Kaire; Marcos-Gragera, Rafael; Vanschoenbeek, Katrijn; Barranco, Miguel Rodriguez; Poch, Ester Oliva; Lillini, Roberto; , The Lung Cancer HR Study Working Group (Frontiers in Epidemiology, 2023)
Objectives: To investigate differences in lung cancer (LC) management and five-year survival using data from European population cancer registries. Methods: Analysis of 4602 lung cancer cases diagnosed in 2010-13, followed up to 2019 in five countries. Multivariable logistic regression to calculate the Odds Ratio (OR) of surgery for stages I-II LC or chemo- or radiotherapy for stages III-IV LC. Relative survival (RS) estimated by the actuarial method; Relative Excess rate of Risk of death (RER), with 95% CI, calculated with generalized linear models. Results: Diagnostic work-up (including diagnostic endoscopy) was extensive for 65.9% patients (57% (Estonia, Portugal) to 85% (Belgium)). For stages I-II, the adjusted OR for surgery (66.5%) decreased with later age and was associated with main bronchus cancer (OR 0.25, CI 0.08-0.82), stage II (OR vs. stage I: 0.42, CI 0.29-0.60), comorbidity (OR vs. absent: 0.55, CI 0.33-0.93), country (ORs: Estonia 1.82, CI 1.28-2.60; Belgium 0.62, CI 0.42-0.91; Portugal 0.69, CI 0.52-0.93). The adjusted five-year RER increased with age and stage and was lower for women (0.78, CI 0.72-0.86); it was above the reference for main bronchus cancer (1.37, CI 1.21-1.54) and unspecified morphology (1.17, CI 1.05-1.30). Surgery carried the lowest mortality (RS 56.9; RER 0.13, CI 0.11-0.15); the RER was above the mean in Estonia (1.20, CI 1.10-1.30) and below it in Portugal (0.88, CI 0.82-0.93) and Switzerland (0.91, CI 0.84-0.99). Comorbidity (1.21, CI 1.09-1.35) and not smoking (0.68, CI 0.57-0.81) were associated with RER. Conclusions: The survival benefit of early diagnosis, allowing curative surgery, was evident at the population level. Survival was higher and surgery less frequent in countries where surgical candidates received a thorough diagnostic work-up. There were no survival differences by morphology, when clinical-pathological factors were adjusted for. Comorbidity and smoking were associated with higher RER. Women had better survival than men.